Survey of fish enemies from three fish farms in Iraq III. Impacts of predaceous water birds on cultivated fishes - Sadek. A. Hussein; Salem, N. K.; Abed, J. M. (Iraqi Journal of Aquaculture, 2022)
The present investigation concerned with a thorough survey on the serious impact of the predaceous water birds from three selected fish farms in the country, namely Al- Manahel fish farm (presently called Al-Beilad) in Babylon province, Basrah University/ Marine Science Center fish farm and Al-Mutawaa fish farm. The latter two are situated in Basrah governorate. Samples were collected on monthly basis for the period from January to October 2002. Impacts of water birds on stocks of cultivated fish species and other faunal components was detected. Stomach of seven species of water birds, namely, herring gull (Larus argentatus), black headed gull (L. ridibundus), slender billed gull (L. genei), little gull (L. minutus), great white heron (Egretta alba ), little egret (E. garzetta) and cormorant (Phalacrocorax carbo sinensis) were examined to calculate food consumption. The study reveals that herring gull occupied first rank in Al–Manahel fish farm followed by cormorant which occupied first rank in Basrah University farm. Fishes formed 100% in food of cormorant, herring gull, black headed gull and slender billed gull. Shrimp was detected in food of little gull and little egret while frogs were consumed by great white heron and little egret. Cormorant occupied first rank in food menu for each birds followed by herring gull and slender billed gull.